Promoting oral cancer awareness and early detection using a mass media approach - Saleh, A.; Yang, Y.H.; Ghani, W.M.N.W.A.; Abdullah, N.; Doss, J.G.; Navonil, R.; Rahman, Z.A.A.; Ismail, S.M.; Abu Talib, N.; Zain, R.B.; Cheong, S.C. (2012)
Background and Aim: Less than 50 of oral cancer cases are diagnosed at early stages of the disease and this is in part due to poor awareness and lack of knowledge on the signs and symptoms of oral cancer. This study sought to measure the baseline awareness of oral cancer in Malaysia and aimed to increase public awareness and knowledge of oral cancer using a mass media campaign. Methods: Baseline awareness and impact of the campaign was measured using self-administered questionnaires sent via email to individuals. The campaign was aired on two national television channels and the reach was monitored through an independent programme monitoring system. Results: 78.2 of respondents had heard of oral cancer, and this increased significantly after the campaign. However, the ability to recognize signs and symptoms remains unchanged. We found that the level of awareness differed between the distinct ethnic subgroups and the reach of the campaign was not uniform across all ethnicities. Conclusion: This substantial study to measure the oral cancer awareness in Malaysia provides important baseline data for the planning of public health policies. Despite encouraging evidence that a mass media campaign could increase the awareness of oral cancer, further research is required to address the acceptability, comprehensiveness and effectiveness. Furthermore, different campaign approaches may be required for specific ethnic groups in a multi-ethnic country such as Malaysia.